SUSTAINABLE DEVELOPMENT AND PERSPECTIVES OF UNIVERSALISTIC TRENDS IN THE MODERN WORLD - Yatsenko, Mikhail; Melnikova, Tatyana; Leopa, Alexander; Gorodishcheva, Anna; Stumpf, Svetlana; Rakhinsky1, Dmitry (Revista Inclusiones, 2020)
The study is devoted to the relevant problem associated with the realization of the universalistic trends in modern time based on the concept of sustainable development. The features of the universalization of social space at the present stage are revealed. They show that these processes are controversial, which actualizes the need to implement the concept of sustainable development. The study focuses on the axiological aspect as an important basis for the universalization of social space. It is proved that without a uniform scale of universal values, it is impossible to form a stable social system. The effects of globalization pressure on countries acting as objects of universalization are shown. Various concepts of the prospects for the development of humanity in the coming decades are explored. The comparative analysis of civilizational, noospheric, and other approaches to creating a single human community is given. It criticizes globalization, which levels the sociocultural identity of individual peoples.